Online whiteboard / Chong Bing Suang - Chong, Bing Suang (2001)
The Network Integrated Whiteboard System is a audio integrated, graphics and network related application. This application creates a new pace on real-time presentation integrated with voice conferencing through networks, which are suitable for lecture presentation and Computer Based Education (CBE). This huge system will divide into three subsystems, or modules, and our team, which are constructed with three members, assign each subsystem to every member. The three subsystem mentioned are the whiteboard module, voice communication module and the server module. Mr. Wong Chan Weng will in charge in the voice communication module while Mr. Lee Chee Ching will cover the server module and I myself will involve in the whiteboard module. The whiteboard module consists of many sub-modules like drawing, writing and typing, imaging, pointing, and graphic effects. My tasks also involve design of graphic user interface (GUI) of the system and make integration of the other modules. We do lots of researches on printed resources or non-printed resources mainly to develop a reliable, secure, maintainable, modifiable, efficient whiteboard application.